-94=8r+3(6-8r)

Simple and best practice solution for -94=8r+3(6-8r) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -94=8r+3(6-8r) equation:


-94=8r+3(6-8r)

We simplify the equation to the form, which is simple to understand
-94=8r+3(6-8r)

Reorder the terms in parentheses
-94=8r+(+18-24r)

Remove unnecessary parentheses
-94=+8r+18-24r

We move all terms containing r to the left and all other terms to the right.
-8r+24r=+18+94

We simplify left and right side of the equation.
+16r=+112

We divide both sides of the equation by 16 to get r.
r=7

See similar equations:

| (2j+3)-4j-(j+3)= | | 2x-3y+z+5a=-9 | | 2x^2-3px-p=0 | | 3x+15=17+x | | 330=-6(1-7x) | | sinx=0.359 | | 2x(2y-11)=80 | | x+5y=3y-2 | | 2n-8(1+3n)=-96 | | -137=-4(1+8m)-5 | | -137=-4(1+8m) | | 17x-3=3x | | 4x+32=-48 | | 84=-4(3+8x) | | 170=-5(1-7n) | | -5(6+2r)-3r=-108 | | 3m=m+10 | | 464=4k-8(8k+2) | | 200=8(1+8n) | | 136=-3(1-7x)-8 | | h(x)=-16x^2+32x+4 | | 85=-6(k-6)-k | | 1x+3y=7.25 | | 6(-8+3a)=-102 | | 154=7(1-3b) | | -91=-7(x+5) | | 5(-3n+5)-3n=-101 | | -4(8p-8)=-160 | | 2s=4rx+8 | | X(2y-11)=80 | | Y=(7+6k)x | | -(-4y-4)-(-3y-8)=4 |

Equations solver categories